Short and practical enantioselective synthesis of linezolid and eperezolid via proline-catalyzed asymmetric alpha-aminooxylation - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of the antibacterials, linezolid (U-100766), and eperezolid (U-100592) using D-proline-catalyzed asymmetric alpha-aminooxylation of aldehydes as the key step is described here. This is the first report on the enantioselective synthesis of linezolid and eperezolid using asymmetric catalysis. (c) 2006 Elsevier Ltd. All rights reserved.